2021
DOI: 10.22603/ssrr.2020-0134
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacies of the Minimal Retroperitoneal Approach for Infectious Spondylodiscitis: A Clinical Case Series

Abstract: An anterior surgical approach for severe infectious spondylodiscitis in the lumbar region is optimal but not always atraumatic. The aim of this study was to evaluate the efficacy and safety of a minimal anterior-lateral retroperitoneal approach, also known as a surgical approach for oblique lumbar interbody fusion, for cases with severe infectious spondylodiscitis with osseous defects. Methods: Twenty-four consecutive patients who underwent anterior debridement and spinal fusion with an autologous strut bone g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Several authors have reported clinical and radiological outcomes of lumbar interbody fusion using an antepsoas approach in pyogenic, fungal, and tuberculous infections of the lumbar spine [ 53 , 54 ]. The theoretical advantages of the antepsoas approach in the spinal infection treatment are as follows: (1) direct visualization and access to infectious tissue in the anterior column, allowing thorough debridement and stable anterior column reconstruction; (2) reduction of surgical morbidity when performed in a minimally invasive surgical (MIS) technique; and (3) avoidance of posterior spinal musculature violation during the posterior approach [ 55 ]. For these reasons, antepsoas lumbar interbody fusion combined with percutaneous pedicle screw fixation has shown superior clinical results, including infection control and complication rates, compared to other surgical techniques in previous studies [ 56 ].…”
Section: Expanding Indications For Olifmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported clinical and radiological outcomes of lumbar interbody fusion using an antepsoas approach in pyogenic, fungal, and tuberculous infections of the lumbar spine [ 53 , 54 ]. The theoretical advantages of the antepsoas approach in the spinal infection treatment are as follows: (1) direct visualization and access to infectious tissue in the anterior column, allowing thorough debridement and stable anterior column reconstruction; (2) reduction of surgical morbidity when performed in a minimally invasive surgical (MIS) technique; and (3) avoidance of posterior spinal musculature violation during the posterior approach [ 55 ]. For these reasons, antepsoas lumbar interbody fusion combined with percutaneous pedicle screw fixation has shown superior clinical results, including infection control and complication rates, compared to other surgical techniques in previous studies [ 56 ].…”
Section: Expanding Indications For Olifmentioning
confidence: 99%
“…However, surgeons should be more cautious when performing this technique for infections that occur at the L5–S1 level. The involvement of the L5–S1 level has been identified as an independent risk factor for unfavorable outcomes following surgical treatment for lumbar pyogenic spondylitis due to difficult surgical access to the lumbosacral junction [ 55 ]. Transperitoneal ALIF with dissection of the major vessels by a vascular surgeon may be preferred over minimally invasive antepsoas lumbar interbody fusion when vascular adhesion to the L5–S1 IVD is suspected on preoperative MRI.…”
Section: Expanding Indications For Olifmentioning
confidence: 99%
“…For minimally invasive removal of the appendicular fecalith in the psoas muscle, we applied a minimal anterolateral retroperitoneal approach, which was used for oblique lumbar interbody fusion. This technique was reported to be also useful in cases of pyogenic spondylitis with severe bone destruction 13 .…”
Section: Discussionmentioning
confidence: 99%